Self-Healing Ability of High-Strength Fibre-Reinforced Concrete with Fly Ash and Crystalline Admixture - T. Chandra Sekhara Reddy Reddy; A Ravitheja Theja; C. Sashidhar (Salehan Institute of Higher Education, 2018)
The aim of this study is to analyse the self-healing capability of high-strength fibre-reinforced concrete (M70) with fly ash and crystalline admixture (CA) in four types of environmental exposures i.e. Water Immersion (WI), Wet-Dry Cycles (WD), Water contact (WC) and Air Exposure (AE). Specimens for four mixes are cast, one mix containing 1.1% of CA and three mixes with 10%, 20% and 30% partial replacement of cement with fly ash and additions of 1.1% CA. The specimens were pre-cracked at 28 days, in the range of 0.10-0.40 mm and the time set for healing was 42 days. The result shows that all the mixes have considerable amount of closing ability and strength-regaining capability for all exposure conditions. The concrete with 20% fly ash and 1.1% CA has complete crack closing ability and 100% strength-regaining capability for WI and WD cycle conditions. From SEM analysis, it is confirmed that self-healing products are CaCO3 and C-S-H gel.